Implications of movement rehabilitation on the quality of life after brainsuses - Krajewski, Piotr (Journal of Education, Health and Sport, 2022)
Introduction: Quality of life is a broad term that covers all functional areas of a stroke patient. Quality of life is primarily determined by the consequences of brain damage, but also by other factors such as age, gender, body weight and time since the stroke. Stroke is the leading cause of disability in adults and the third leading cause of death. Because of its effects, it is one of the most serious diseases of the nervous system. Most frequently affected are people who work in different social roles in their working environment. Worldwide, there are more than 55 million survivors of a stroke, half of whom have a significant impact on the continued functioning of daily life. Material and methods : The data show that 100% of respondents have had a stroke, which means they are able to make more accurate statements about rehabilitation problems. Stroke occurred in up to one in 10% of respondents. between one and three years in 15%, between three and five years in 55% of the population studied. Over five years at 20%. The participants are people who have undergone rehabilitation shortly after a stroke and some have it to this day. Results: According to the respondents in this study, the improvement in social role competence was very strong – 7%, large – 18%, medium – 44%, small – 18%, none – 13%. At the same time, it was found that rehabilitation restored the lost functions of everyday life to the interviewees with a high degree – 60%, average – 27%, low – 13%. Rehabilitation should be an integral part of the treatment in order to adapt to the needs of the patient. In order to achieve a significant improvement, it is important to carry out the therapy systematically and for longer. These measures are taken to restore maximum or full performance, but this is not always possible. Much depends on the age of the patient, the previous and current diseases, the changes after the stroke, and the frequency and duration of rehabilitation. In summary, stroke rehabilitation is very important – it not only protects life and reduces the risk of death, but also guarantees an improvement in the quality of life. Conclusions: Research results clearly show that rehabilitation after a stroke is very important to restore health and well-being while increasing mobility at the same time. However, respondents differed from each other, which means that it is difficult to fully compare the results. Age, the consequences of a stroke and the time after rehabilitation after a stroke have certainly influenced this.